2021
DOI: 10.1186/s12958-021-00721-4
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological experience and coping strategies of patients in the Northeast US delaying care for infertility during the COVID-19 pandemic

Abstract: Background On March 17, 2020 an expert ASRM task force recommended the temporary suspension of new, non-urgent fertility treatments during an ongoing world-wide pandemic of Covid-19. We surveyed at the time of resumption of fertility care the psychological experience and coping strategies of patients pausing their care due to Covid-19 and examined which factors were associated and predictive of resilience, anxiety, stress and hopefulness. Methods C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
3
14
0
5
Order By: Relevance
“…Furthermore, the demographic information of our sample is similar to that of the German population seeking fertility treatment [25]. Although the overall response rate (participants that clicked on the link and then completed the questionnaire) of 42% is relatively low, it is similar to other studies conducted on the same subject [8,9,17]. Additionally, our response rate is likely to be an underestimate, as people were able to click on the link multiple times or could have clicked on it and decided that they were not eligible.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Furthermore, the demographic information of our sample is similar to that of the German population seeking fertility treatment [25]. Although the overall response rate (participants that clicked on the link and then completed the questionnaire) of 42% is relatively low, it is similar to other studies conducted on the same subject [8,9,17]. Additionally, our response rate is likely to be an underestimate, as people were able to click on the link multiple times or could have clicked on it and decided that they were not eligible.…”
Section: Discussionmentioning
confidence: 64%
“…While there have been studies concerning the emotional impact of the suspension of treatments [7][8][9][11][12][13], this is the first to have been conducted in Germany where, in 2020, incidence and case fatality rates were relatively low compared to many other European countries [14]. To our knowledge, it is the first study to assess the possible worries that fertility treatment patients might have concerning an infection with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our study reported significantly lower PSS scores among women who received social support from their spouses. Similarly, a survey of American women whose fertility treatment was paused during the pandemic showed that those with stronger support systems and who employed effective coping strategies to deal with the treatment delay demonstrated more resilience, less perceived stress, and less anxiety [ 23 ]. Coping strategies can be taught to affected women by creating liaisons with mental health professionals in anticipation of further treatment interruptions.…”
Section: Discussionmentioning
confidence: 99%